Platelet protease-activated receptor 4 genotype and response to aspirin in pregnancy - Rupsa C. Boelig; James V. Michael; Antonios Tawk; Tingting Zhan; Joanna S. Y. Chan; Walter K. Kraft; Steven E. McKenzie (Blood Vessels, Thrombosis & Hemostasis)
Abstract: The platelet protease-activated receptor 4 (PAR4) threonine 120 (Thr120) allele is an activating allele associated with reduced aspirin response in vitro. Aspirin is recommended in high-risk pregnancies to prevent preeclampsia and preterm birth. We evaluated the impact of PAR4 genotype on aspirin response in pregnancy, as measured by platelet function assay 100 (PFA-100) epinephrine closure time, and perinatal outcomes. We conducted a prospective cohort study of high-risk pregnant patients who took 81-mg aspirin daily. PFA-100 was assessed at baseline, 2 to 4 weeks after aspirin initiation (follow-up 1), and 28 to 32 weeks’ gestation (follow-up 2). Primary outcome was difference in PFA-100 by genotype. Exposure was defined as PAR4-Thr120 homozygous vs not. Of the 122 participants were included, 24 (19.6%) were PAR4-Thr120 homozygous, and 106 completed follow-up 1 with >75% adherence. Participants homozygous for PAR4-Thr120 had a significantly higher rate of prior preterm birth (50.0% vs 16.1%; P = .004). Genotype was not significantly associated with PFA-100 response in multivariable regression. In the subset with urinary thromboxane data available (n = 18), thromboxane levels were higher in those who were homozygous vs not (geometric mean ratio, 208 [95% confidence interval, 1.66-2.61]; P < .001) in multivariable regression. There was a higher rate of placental intervillous thrombosis, although not statistically significant (16.7% vs 3.9%; P = .08). Patients homozygous for PAR4-Thr120 had a higher incidence of prior preterm birth, a risk factor for poor perinatal outcome. Aspirin response, measured by PFA-100, was similar across genotypes, although Thr120 homozygosity may be associated with reduced thromboxane suppression and a higher rate of placental vasculopathy even with 81-mg aspirin daily.